2020
DOI: 10.1002/sctm.20-0102
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of bone marrow mononuclear cell transplantation combined with interventional education for autism spectrum disorder

Abstract: The aim of this study was to evaluate the safety and efficacy of autologous bone marrow mononuclear cell transplantation combined with educational intervention for children with autism spectrum disorder. An open-label clinical trial was performed from July 2017 to August 2019 at Vinmec International Hospital, Hanoi, Vietnam. Thirty children who fulfilled the autism criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, and had Childhood Autism Rating Scale (CARS) scores >37 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…Comparable to our treatment approach applying autologous BM-derived intrathecally applied SCT, two investigations -one applying a single (14) and the other two-intrathecal (15) stem cell instillations also reported encouraging results. Mixed results were reported using intravenous delivery of either, autologous or allogenic, umbilical cord blood-derived SCT.…”
Section: Efficacy Of the Proceduresmentioning
confidence: 72%
See 3 more Smart Citations
“…Comparable to our treatment approach applying autologous BM-derived intrathecally applied SCT, two investigations -one applying a single (14) and the other two-intrathecal (15) stem cell instillations also reported encouraging results. Mixed results were reported using intravenous delivery of either, autologous or allogenic, umbilical cord blood-derived SCT.…”
Section: Efficacy Of the Proceduresmentioning
confidence: 72%
“…Sharma et al (14) in a group of 34 children reported asides minor side effects including nausea, vomiting, and local pain, a percentage of major adverse events in 31% (10/32) comprising hyperactivity and epileptic seizures. Thanh et al (15) reported no major adverse event in similarly sized study on 30 children undergoing repeated interventions. In our pilot study we encountered neither immediate, nor delayed major adverse events.…”
Section: Immediate and Delayed Complicationsmentioning
confidence: 95%
See 2 more Smart Citations
“…A clinical study examining the efficacy of autologous bone marrow mononuclear cell transplantation (BMMNC) in thirty children who fulfilled the autism criteria with Childhood Autism Rating Scale (CARS) scores >37 reported a significant reduction in the severity of ASD with the median CARS score decreasing from 50 (range 40–55.5) to 46.5 (range 33.5–53.5) ( p < 0 .05) [ 108 ]. Another study assessing the (BMMNC) transplantation infused via the intrathecal route in 32 children with ASD noticed improvements in speech, language patterns, social relationships, and brain metabolism.…”
Section: Resultsmentioning
confidence: 99%